1965
DOI: 10.1017/s0022172400045046
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in acute respiratory infection in a general community

Abstract: The aetiology of acute respiratory infections between September 1962 and August 1963 was studied in two general practices in Cambridge. These practices were reasonably representative of the permanent community of Cambridge.There were 592 spells of acute respiratory infection in the combined practices, representing an incidence of 11·4 spells per 100 persons. Children aged 0–4 had the highest rates (51·6 spells per 100 persons).It was possible to establish a diagnosis in 62·5% of cases investigated. Influenza a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Respiratory syncytial virus was isolated in their study but not in the present one and this accounts for part of the difference. Banatvala et al (1965) reported a virus isolation rate of 28 2%' but this included two epidemics, one caused by influenza and the other by parainfluenza viruses. In the report of the M.R.C.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory syncytial virus was isolated in their study but not in the present one and this accounts for part of the difference. Banatvala et al (1965) reported a virus isolation rate of 28 2%' but this included two epidemics, one caused by influenza and the other by parainfluenza viruses. In the report of the M.R.C.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we focused on five viruses that are the major causes of acute respiratory disease, including influenza, parainfluenza, rhinovirus, adenovirus, and respiratory syncytial virus (RSV) [ 19 ]. These viruses share a relatively short incubation period (1–4 days) and a person-to-person mode of transmission.…”
Section: Introductionmentioning
confidence: 99%